Primary extraskeletal myxoid chondrosarcoma of the breast: report of a case and literature review - Sharma*, Shivani; Sharma*, Anurag; Lobo*, Anandi; Sampat, Nakul Yogeswar; Kumar, Mohit; Kajla, Ramkrishan; Mohapatra, Satya Sunder; Mohanty, Sambit Kumar (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2022)
Primary extraskeletal myxoid chondrosarcoma (pEMC) of the breast is rare and only a few cases have been reported to date. Herein, we report a case of primary EMC of the breast in a 45-year-old female. The patient presented with a left breast mass for 1 month. Mammogram revealed a fairly circumscribed mass with spicules of calcifications. The core biopsy and resection specimen showed a myxoid soft tissue neoplasm with histologic features of a myxoid chondrosarcoma. Necrosis, hemorrhage, and brisk mitotic activity were present. No malignant epithelial element was identified even after extensive sampling. The tumor cells exhibited immunoreactivity for vimentin, S100, neuron specific enolase, CD99, and synaptophysin, while the epithelial, myoepithelial, and mammary lineage-associated markers were negative. As up to 81% of EMC cases harbor t(9;22)(q22;q12), this results in a fusion of EWS RNA-binding protein 1 gene (EWSR1) at 22q12 to the nuclear receptor subfamily 4, group A, member 3 gene at 9q22. A rearrangement involving the EWSR1 locus was detected in our case. Whole body PET-CT did not reveal any other mass. A diagnosis of pEMC was rendered. The patient received six cycles of 5-Fluorouracil, Cyclophosphamide, and Adriamycin. The patient was in clinical and radiologic remission at the last follow-up (18 months post surgery). PET-CT and brain MRI were negative. In conclusion, surgical pathologists should include EMC in their differential while dealing with a myxoid soft tissue lesion of the breast, particularly in the core needle biopsies. An expeditious diagnosis of EMC of the breast would allow the surgeon to carry out conservative breast surgery instead of more radical approaches taken in cases of other primary malignant mammary neoplasms.